2009
DOI: 10.1017/s1355617709090262
|View full text |Cite
|
Sign up to set email alerts
|

Progressive decline of decision-making performances during multiple sclerosis

Abstract: The purpose of this study was to evaluate longitudinally, using the Iowa Gambling Task (IGT), the dynamics of decision-making capacity at a two-year interval (median: 2.1 years) in a group of patients with multiple sclerosis (MS) ( n = 70) and minor neurological disability [Expanded Disability Status Scale (EDSS) ≤ 2.5 at baseline]. Cognition (memory, executive functions, attention), behavior, handicap, and perceived health status were also investigated. Standardized change scores [(score at retest-score at ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
27
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 12 publications
5
27
0
3
Order By: Relevance
“…The proportion of progressive MS forms in the present study was also very low (9/84, 10.7%). A decline in decision-making process early in the disease was also noted in 11 but in this study, authors could not relate the dysfunction in the decision-making process to executive or other cognitive impairments.…”
Section: Discussionmentioning
confidence: 60%
“…The proportion of progressive MS forms in the present study was also very low (9/84, 10.7%). A decline in decision-making process early in the disease was also noted in 11 but in this study, authors could not relate the dysfunction in the decision-making process to executive or other cognitive impairments.…”
Section: Discussionmentioning
confidence: 60%
“…Little is known about the natural history of DM disturbances in MS; as mentioned, the study population comprised mostly recently diagnosed patients with MS. One longitudinal study reassessing IGT scores at 2-year intervals showed that DM deficits could progress over time 27. Interestingly, IGT performance in primary progressive MS (PPMS) seems to be significantly affected compared to HC and secondary progressive MS (SPMS),38 highlighting the heterogeneous nature of DM impairments.…”
Section: Discussionmentioning
confidence: 99%
“…In the latter, several studies have reported impaired DM under ambiguous conditions even in the absence of major mood, cognitive or physical impairment. Moreover, Simioni and colleagues showed that a decline in DM capacity under ambiguity can appear as an early deficit in patients with MS, and when retested after 2 years, individuals can show significant deterioration in IGT scores independently of other markers of cognitive, emotional or disability worsening 27. The study by Nagy and colleagues also reports that DM impairment in patients with MS can appear as an isolated deficit without the presence of generalised cognitive impairment and that this deficit is unrelated to executive function, as they did not detect a significant correlation between IGT scores and the Wisconsin Card Sorting Test 25…”
Section: Introductionmentioning
confidence: 99%
“…Decision making was assessed using the Iowa Gambling Task (IGT; Bechara, Damasio, Damasio, & Anderson, 1994), which measures reward-based learning and decision making based on evaluation of long-term outcomes. PwMS have displayed impaired decision-making ability using the IGT (Kleeberg et al, 2004;Simioni et al, 2009). …”
Section: Cognition/executive Functionmentioning
confidence: 99%